The relationship between basic psychological needs satisfaction and university students’ academic engagement: The mediating effect of emotional intelligence - Chen, Hongxia; Zhang, Morning Hon (Frontiers in Psychology, 2022)
Introduction Basic psychological needs satisfaction (BPNS) and Emotional intelligence (EI) have been underscored as helpful psychological constructs in explaining academic engagement. However, the joint interaction of BPNS with EI abilities to explain academic engagement has not been tested. Therefore, the present study aimed to investigate the interactive role of BPNS with EI abilities in the prediction of academic engagement in a sample of Chinese university students. Methods A questionnaire survey was administered to a sample of 466 university students. The data were analyzed using the SPSS (version 21.0) software. The first analysis consisted of descriptive statistics (including mean and standard deviation) and Pearson’s correlations among BPNS, EI, and academic engagement. Through structural equation modeling (SEM), direct and indirect effects were calculated. Results The results showed that BPNS was positively associated with academic engagement and that only the Use of emotion dimension of EI mediated these associations. Discussion These results suggest that important interventions incorporated with BPNS and EI abilities, especially the use of emotion ability, may be performed to promote university students’ academic engagement.